From here to eternity [videorecording (DVD)] - Zinnemann, Fred, 1907-1997; Lancaster, Burt, 1913-1994; Sinatra, Frank, 1915-1998; Kerr, Deborah, 1921-2007; Clift, Montgomery; Reed, Donna, 1921-1986; Borgnine, Ernest, 1917-2012; Jones, James, 1921-1977 (Columbia TriStar Home Entertainment, 2001)
Drama about life in the Army in the days prior to World War II. Shows the effect of Army discipline on an individualistic former boxing champion who defies the attempts of officers and men to break him when he refuses to fight on the company's boxing team. Includes actual scenes of the Japanese attack on Pearl Harbor.